ANALISIS KADAR FENOLIK TOTAL DAN FLAVONOID TOTAL EKSTRAK ETANOL KULIT PISANG KEPOK (Musa pradisiaca L) - Ariani, Novia; Prihandiwati, Erna; Rahim, Aulia; Milasari, Novi; Fatimah, Nurul (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Banana peel is a very large amount of waste material (banana fruit waste). In general, banana peels have not been used optimally. Based on the research results, kepok banana peel contains secondary metabolites in the form of flavonoids, alkaloids, tannins and saponins. This study aims to determine the total phenolic content and total flavonoid content of the ethanol extract of kepok banana skin (Musa pradisiaca L). Extraction was carried out by maceration method with 96% ethanol solvent. Determination of total phenol content used the Folin-Ciocalteu method with gallic acid as comparator compound and the determination of total flavonoid content used the colorimetric method with 10% AlCl3 and 5% acetic acid as reagents. The results showed that kepok banana peel extract had an average total phenolic content of 13.4495 mg GAE/g Â± 1.5473206 and an average total flavonoid content of 8.5468 mg QE/g Â± 0.947422695.